2017
DOI: 10.1007/978-1-4939-7274-6_29
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian Randomization

Abstract: Confounding and reverse causality have prevented us from drawing meaningful clinical interpretation even in well-powered observational studies. Confounding may be attributed to our inability to randomize the exposure variable in observational studies. Mendelian randomization (MR) is one approach to overcome confounding. It utilizes one or more genetic polymorphisms as a proxy for the exposure variable of interest. Polymorphisms are randomly distributed in a population, they are static throughout an individual'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 40 publications
1
78
0
Order By: Relevance
“…A more recently suggested method to approach this problem is the Mendelian randomization (MR) design 5, 6, 7. Basically, one or a number of genetic variants are identified that can act as instrumental variables for the risk factor in that they are associated with the risk factor, but have no direct effect on PD.…”
mentioning
confidence: 99%
“…A more recently suggested method to approach this problem is the Mendelian randomization (MR) design 5, 6, 7. Basically, one or a number of genetic variants are identified that can act as instrumental variables for the risk factor in that they are associated with the risk factor, but have no direct effect on PD.…”
mentioning
confidence: 99%
“…altered glucose metabolism or body mass index) and an outcome (e.g. PD) 13,14 . In principle, MR allows the use of genetic variants as proxy representatives of exposure from one population to test an association with an outcome in a completely independent population 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The MR employs genetic variants as randomized proxy markers of risk factors, also known as genetic instruments to check for directionality in a relationship between a risk factor such as educational attainment and a disease or outcome like AD or PD 10 . Using the largest cohorts on AD and PD available to date, educational attainment was most recently shown to play a protective casual role in AD and risky casual role in PD 8,9 .…”
Section: Introductionmentioning
confidence: 99%